Pemikiran Ekonomi Abu Ubaid dan Abu Yusuf Serta Relevansinya Terhadap Perekonomian di Indonesia - Alya Amelia; Irawati; Andi Hilal Miftah Fauzan (Yayasan Darussalam Patalassang, 2025)
This research aims to examine the economic thoughts of Abu Ubaid and Abu Yusuf. This research uses a literature study method with a focus on the Islamic economic thought of Abu Ubaid and Abu Yusuf and its relevance to the economy in Indonesia. The results of this research show that Muslim intellectual figures have contributed significantly to the development of Islamic economics, especially in the fields of taxation, public finance and business ethics. Their works are still relevant and serve as a reference in discussions about Islamic economics. One of the works of Abu Ubaid and Abu Yusuf is kita al-Amwal and kitab al-Kharaj. The book al-Amwal discusses the principles of Islamic economics, including the concepts of zakat, infaq and alms. Kirab al-Kharaj discusses the principles of taxation in Islam, including the concepts of kharaj, jizyah, and zakat.